Delayed cord clamping in South African neonates with expected low birthweight: a randomised controlled trial. Issue 2 (2nd November 2014) - Tiemersma, Sybrich; Heistein, Julia; Ruijne, Roos; Lopez, Gustavo; van Lobenstein, Jeroen; van Rheenen, Patrick
Abstract Objective To evaluate safety and haematological effects of delayed cord clamping (DCC) in infants with expected low birthweight born in a resource‐poor setting. Methods Randomised controlled trial involving pregnant women in early labour ≥18 years with intrapartum symphysal‐fundal height ≤32 cm. Mothers were randomised for either early cord clamping (ECC, <30 s) or DCC (2–3 min after birth). Results We included 104 vigorous infants born by vaginal delivery, of whom 39% had a birthweight <2500 g. Infant haemoglobin (Hb) levels 24 h after birth were significantly higher in the DCC group (18.0 g/dl vs 16.8 g/dl, P = 0.006). Despite successful placental transfusion, hyperbilirubinemia and hyperviscosity were not observed. Two months after birth, there were no differences in Hb between groups (9.9 g/dl vs 9.8 g/dl, P = 0.60), but the infants in the DCC group had better weight gain from baseline than those with ECC (2.2 kg vs 1.9 kg, P = 0.058). Conclusions In this South African cohort of newborns with a subnormal distribution of birthweight delayed cord clamping was a safe procedure. Two months after birth the effect of DCC on Hb was not detectable anymore. DCC should be promoted in every singleton delivery in a resource‐poor setting irrespective of the birthweight.